2011
DOI: 10.1177/0038038510387197
|View full text |Cite
|
Sign up to set email alerts
|

Finding Prosperity as a Lottery Winner: Presentations of Self after Acquisition of Sudden Wealth

Abstract: The narrative about the squandering lottery winner ending up alone and in debt has been shown to affect other lottery winners’ thinking about how to manage their money. Based on a narrative analysis of interviews with 14 Swedish lottery winners, this article considers the ways in which lottery winners present themselves and their post-winning life in counter-position to this story about the squandering winner. By spending their prize money responsibly in order to project moderate, non-luxury consumption, the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Casey (2003: 246) states that 'it is extremely difficult to find any sociological analysis' on lottery play. Yet a small body of sociological research does actually exist (Casey, 2003(Casey, , 2006(Casey, , 2008Garvía, 2007;Hedenus, 2011;Light, 1977;Nibert, 2000;Reith, 1999;Sallaz, 2009). However, while most of this research provides insightful historical or ethnographic accounts on lottery gambling, quantitative approaches that test sociological theories on why people play the lottery have been scant.…”
mentioning
confidence: 99%
“…Casey (2003: 246) states that 'it is extremely difficult to find any sociological analysis' on lottery play. Yet a small body of sociological research does actually exist (Casey, 2003(Casey, , 2006(Casey, , 2008Garvía, 2007;Hedenus, 2011;Light, 1977;Nibert, 2000;Reith, 1999;Sallaz, 2009). However, while most of this research provides insightful historical or ethnographic accounts on lottery gambling, quantitative approaches that test sociological theories on why people play the lottery have been scant.…”
mentioning
confidence: 99%
“…Stories about freedom and happiness can, furthermore, be interpreted from a liberal notion of ‘money as a liberator from imposed social structures’, while stories about greed and discord, envy and ill, will spring upon an understanding of money as harmful to social relations (Binde : 222). In a similar way, studies on lottery winners establish how winners strive to balance their spending; both in relation to self‐serving ideals of a consumer society and to more austere ideals derived from the Protestant work ethic (Abrahamson ; Hedenus ; Bauman ; Reith ; Weber ). By prudential spending of their windfall money, rationalizing and justifying any more extravagant expenditures, and keeping to a ‘low‐profile consumption’, the winners can thus uphold their social positions and avoid the risk of social deviance (cf.…”
Section: Gamblers Lottery Winners and Lottery Prize Moneymentioning
confidence: 99%
“…Opposing the notion that money and consumption enable people to present themselves as belonging to higher classes, Casey () showed that her respondents frequently rejected and criticized the middle and upper class way of life. Even among people who have been fortunate enough to cash in a large prize, there is talk about the windfall as something that puts themselves, or other winners, at risk of ‘losing their heads’ (Hedenus ; Falk and Mäenpää ).…”
Section: Gamblers Lottery Winners and Lottery Prize Moneymentioning
confidence: 99%
See 2 more Smart Citations